2011
DOI: 10.1016/j.mce.2010.12.034
|View full text |Cite
|
Sign up to set email alerts
|

New and translational perspectives of oestrogen deprivation in breast cancer

Abstract: Please cite this article as: Dunbier, A.K., Martin, L.-A., Dowsett, M., 'New and translational perspectives of oestrogen deprivation in breast cancer', Molecular and Cellular Endocrinology (2010),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…However, 50p3 β cells demonstrated minimal growth induction following steroid hormone treatment. Estrogen independence developed 9–12 weeks after initiation of selection in Veh cells (data not shown), consistent with previous reports [6, 20]. The emergence of estrogen independence in 1pE and 50p3 β cells was delayed, developing after 6–7mo of selection and 4–5mo selection, respectively (data not shown).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…However, 50p3 β cells demonstrated minimal growth induction following steroid hormone treatment. Estrogen independence developed 9–12 weeks after initiation of selection in Veh cells (data not shown), consistent with previous reports [6, 20]. The emergence of estrogen independence in 1pE and 50p3 β cells was delayed, developing after 6–7mo of selection and 4–5mo selection, respectively (data not shown).…”
Section: Resultssupporting
confidence: 91%
“…Dose–response curves were generated for E2- or 3 β Adiol-induced proliferation for each cell line to determine whether any of the selection lines had developed hypersensitivity to low concentrations of steroid hormone for growth induction, as previously reported [6, 20]. Minor increases in sensitivity (<1-log decrease in EC 50 ) were observed versus parental MCF-7 cells in all selections except 50pE cells, consistent with their parallel phenotype to parental MCF-7 cells (Supplementary Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…While oestrogen is a recognized mitogen that usually stimulates mammary cell proliferation and inhibits apoptosis through activation of the oestrogen receptor, 1 both preclinical 38–42 and clinical 41 findings suggest that after long-term oestrogen deprivation, adaptive changes in mammary tumor gene expression profiles render tumors paradoxically susceptible to oestrogen-induced apoptosis. 39,40 While the mechanisms are complex and not completely understood, 42 preclinical studies suggest involvement of the Fas/Fas L extrinsic (receptor-mediated) death regulatory pathway 43 and the intrinsic (mitochondrial) apoptotic pathway, mediated via increased expression of several pro-apoptotic proteins including PUMA (p53-unregulated modulator of apoptosis). 44,45 …”
Section: Discussionmentioning
confidence: 99%
“…These apparently paradoxical results are consistent with findings emerging from preclinical studies which have identified complex, time dependent effects of changes in the estrogen environment on the influence of estrogen on mammary tissue. While estrogen commonly stimulates breast cell proliferation and inhibitsapoptosis, under conditions of estrogen deprivation,gene expression profile changes occur such that estrogen then inducesrather than inhibits apoptosis (40, 55, 56). In addition, estrogen deprivation can also result in increased estrogen receptor sensitivity, such thatrelatively low estrogen levels are sufficient to stimulate the estrogen pathway and accelerate mammary tumor growth (57).…”
Section: Potential Mediating Mechanisms Of Action On Hormone Therapy mentioning
confidence: 99%